Primary school teachers' knowledge and misperceptions of attention-deficit/hyperactivity disorder (ADHD) - Kleynhans, Sandra E. (Stellenbosch : University of Stellenbosch, 2007)
Thesis (MA (Psychology))--University of Stellenbosch, 2005.